Rare, Endangered, Endemic, and Protected Species (REEPS) conservation in the Cisokan, West Java, Indonesia - TEGUH HUSODO; ERRI NOVIAR MEGANTARA; ASEP ZAINAL MUTAQIN; DWI RUSTAM KENDARTO; SUSANTI WITHANINGSIH; INDRI WULANDARI; SYA SYA SHANIDA; PUPUT FEBRIANTO (Society for Indonesian Biodiversity, 2024)
Abstract. Husodo T, Megantara EN, Mutaqin AZ, Kendarto DR, Withaningsih S, Wulandari I, Shanida SS, Febrianto P. 2024. Rare, Endangered, Endemic, and Protected Species (REEPS) conservation in the Cisokan, West Java, Indonesia. Biodiversitas 25: 5094-5102. The Upper Cisokan Pumped Storage (UCPS) hydropower construction poses significant challenges to local biodiversity, particularly Rare, Endemic, Endangered, and Protected Species (REEPS). This study aimed to describe the distribution of REEPS threatened by the construction and analyze the trend of their presence during the development. Methods applied include sign surveys, camera trapping, and literature review across a 47-grid study area. The findings show that ten REEPS continue to occupy forest patches and corridors despite ongoing construction activities. All REEPS species were consistently recorded from 2009 to 2022, indicating that their habitat can still meet their survival needs. However, habitat fragmentation and overlapping land use due to construction threaten these species' long-term sustainability. The grid-based analysis identified nine grids as core habitats for multiple REEPS species, emphasizing the need for ongoing biodiversity management. This includes preserving critical corridors and forest patches, which are crucial for the survival of these species. Long-term monitoring ensures coexistence between wildlife and human activities, maintaining ecosystem balance while advancing the hydropower project. This study highlights the importance of integrating wildlife conservation with infrastructure development in biodiversity-rich areas.